A Computational Study of the Hemodynamic Impact of Open‐ Versus Closed‐Cell Stent Design in Carotid Artery Stenting. Issue 7 (12th April 2013) - De Santis, Gianluca; Trachet, Bram; Conti, Michele; De Beule, Matthieu; Morbiducci, Umberto; Mortier, Peter; Segers, Patrick; Verdonck, Pascal; Verhegghe, Benedict
Abstract The aim of this study is to analyze the shape and flow changes of a patient‐specific carotid artery after carotid artery stenting (CAS) performed using an open‐cell (stent‐O) or a closed‐cell (stent‐C) stent design. First, a stent reconstructed from micro‐computed tomography (microCT) is virtually implanted in a left carotid artery reconstructed from CT angiography. Second, an objective analysis of the stent‐to‐vessel apposition is used to quantify the lumen cross‐sectional area and the incomplete stent apposition (ISA). Third, the carotid artery lumen is virtually perfused in order to quantify its resistance to flow and its exposure to atherogenic or thrombogenic hemodynamic conditions. After CAS, the minimum cross‐sectional area of the internal carotid artery (ICA) (external carotid artery [ECA]) changes by +54% (−12%) with stent‐O and +78% (−17%) with stent‐C; the resistance to flow of the ICA (ECA) changes by −21% (+13%) with stent‐O and −26% (+18%) with stent‐C. Both stent designs suffer from ISA but the malapposed stent area is larger with stent‐O than stent‐C (29.5 vs. 14.8 mm2). The untreated vessel is not exposed to atherogenic flow conditions whereas an area of 67.6 mm2 (104.9) occurs with stent‐O (stent‐C). The area of the stent surface exposed to thrombogenic risk is 5.42 mm2 (7.7) with stent‐O (stent‐C). The computer simulations of stenting in a patient's carotid artery reveal a trade‐off between cross‐sectional size and flow resistance of the ICA (enlarged and circularized) and the ECA (narrowed and ovalized). Such a trade‐off, together with malapposition, atherogenic risk, and thrombogenic risk is stent‐design dependent.